Survival Rate of Patients with Cardiothoracic Injuries in Road Traffic Accidents, and their Relationship with ISS, GCS and blood transfusions. - Khalid Fahad Almalki; Abdullah Mussad Alharbi; Anthony Morgan; Adel Mohammed Bin Sultan; Saud Ayedh Alajmi; Turke Ali Alajmi; Arif Mohammed Alanazi; Mohammed Ibrahim Alsheddi; Ali Abdulaziz Alanzan; Zayed Fahd Al-Dosari (Medičnì Perspektivi, 2018)
Severe thoracic trauma is one of the major causes of injury-related mortality. In the United States, thoracic trauma results in one-fourth of all trauma deaths. Globally, cardiothoracic trauma is also a major contributor to mortality. The most common cardiothoracic injuries include rib fractures, thoracic vertebral fractures, haemothorax, pneumothorax, flail chest, and lung contusions. The purpose of the present study was to determine the survival rate of patients with cardiovascular injuries in road traffic accidents and its relationship with ISS, GCS and blood transfusions at King Khalid Hospital. This study is a useful addition to the literature, as research in this topic is lacking. A total of 189 patients were transported to the hospital with cardiothoracic injuries during the study period. Data was gathered regarding age, gender, nationality, vehicle user type, anatomical region injured, Intensive Care Unit (ICU) admission, Glasgow Coma Scale (GCS), Injury Severity Score (ISS), blood transfusion, treatment and mortality rate. The neurological status was assessed using the GCS score. Injury Severity Scores were calculated to categorize the injury severity. The mean patient age was 31.81 years, with a peak age of between 21–30 years. Males predominated (93.7%) with a male to female ratio of 15:1. Most of the patients were Saudi nationals (61.3%). Overall mortality was 7.9%. Factors that were significantly associated with mortality were head and neck involvement, ICU admission, age (above 60), treatment delivered, and blood transfusions. Cardiothoracic trauma is associated with a high mortality rate, which may depend on the clinical presentation such as GCS, ISS, degree of shock, pattern of injuries, and associated injuries. Immediate management is vital for patients with life-threatening cardiothoracic trauma, as mortality is high if the diagnosis is missed, wrong or left untreated.